Students’ Perception on English Teaching Effectiveness in the Classroom Activities at SMP Negeri 4 Kota Gorontalo - Miolo, Sartin; Dirgahayu, Nitha; Malik, Harto (Transbahasa, 2022)
This research is aimed to find out the students’ perception on English teaching effectiveness in the classroom activities. This research sought students' perceptions on teaching effectiveness in the classroom activities which prompt the utilization of mixed-method. This research was conducted at SMP Negeri 4 Kota Gorontalo. In conducting this research, the participants were the eighth-grade students in SMP Negeri 4 Gorontalo. The eighth-grade in SMP Negeri 4 Kota Gorontalo itself is divided into five classes in which every class contains 25-30 students. The number of participants were 40 students selected from five classes of the eighth-grade. The data was collected using questionnaire and analysed using scoring, analysing problems, and concluding/interpreting. The results showed that English teaching effectiveness in the classroom is good. It was judged from four indicators of effectiveness itself. Those were instructional delivery, student assessment, learning environment, and personal qualities. Based on the research, the four indicators of effectiveness were categorized well. It was proven by the fact that most of the students in the position of agree.